Eco Enzyme: Upaya Pemanfaatan Limbah Rumah Tangga Untuk Kesehatan Masyarakat Desa Pecangakan - Komarudin, Ahmad; Asrori; Hikmah, Fitri Nur; Sadiah, Khalimatus; Muhbahri, M. Tommi (Profetik: Jurnal Pengabdian Masyarakat, 2023)
Ecoenzymes use cheap and easy-to-obtain raw materials, especially in the household environment. The fermentation process, which takes up to three months, is quite a long time. However, the resulting solution has many benefits, especially for health. In the process alone, it can produce gas O3 (Ozone). This gas is needed by the earth for the sustainability of the ecosystem. Ecoenzyme solution when mixed with water, will react and can produce a liquid that can be used for cleaning. Starting from floor cleaners, clothes, bath soap, agricultural medicines and so on. This solution when mixed to water the plants will produce fruit and better yields. In addition, this solution can also be used to repel pests in the fields, such as insects, birds and so on. Another benefit is that if the organic waste is used after fermentation, it can be used for organic fertilizer. The benefits of ecoenzymes apart from being environmentally friendly can also generate economic value for the people of Pencangakan Village, Adiwena District, Tegal Regency. By popularizing the use of household waste through ecoenzymes to the public. It is hoped that this product will be utilized by the surrounding community and the wider community so that it can benefit all